2015
DOI: 10.1017/s0960258514000427
|View full text |Cite
|
Sign up to set email alerts
|

Secondary dormancy inBrassica napusis correlated with enhancedBnaDOG1transcript levels

Abstract: Dormancy has evolved in plants to restrict germination to favourable growth seasons. Seeds from most crop plants have low dormancy levels due to selection for immediate germination during domestication. Seed dormancy is usually not completely lost and low levels are required to maintain sufficient seed quality. Brassica napus cultivars show low levels of primary seed dormancy. However, B. napus seeds are prone to the induction of secondary dormancy, which can lead to the occurrence of volunteers in the field i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…Née et al . () also detected BnaDOG1 transcripts during seed development, but concluded that expression of BnaDOG1 was not sufficient for induction of dormancy. However, the highest BnaDOG1 transcript levels were found between about 37 and 44 DAP, and they decreased to very low levels from 51 to 56 DAP.…”
Section: Are Brassica Napus Seeds Nondormant At Maturity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Née et al . () also detected BnaDOG1 transcripts during seed development, but concluded that expression of BnaDOG1 was not sufficient for induction of dormancy. However, the highest BnaDOG1 transcript levels were found between about 37 and 44 DAP, and they decreased to very low levels from 51 to 56 DAP.…”
Section: Are Brassica Napus Seeds Nondormant At Maturity?mentioning
confidence: 99%
“…Née et al . () reported that the gene BnaDOG1 ( B. napus DELAY OF GERMINATION1 ) plays a role in the induction of secondary dormancy in B. napus . Née et al .…”
Section: Are Brassica Napus Seeds Nondormant At Maturity?mentioning
confidence: 99%
“…On the other hand, although dog1 loss-of-function mutants have a strong non-dormant phenotype (Bentsink et al 2006), it does not exclude that there may exist some factor(s) different to DOG1 required in triggering and maintaining of dormancy which still is present during AR0 imbibition. This possibility was recently conjectured in B. napus for the induction of primary dormancy (Née et al 2015). Interestingly, the AtDOG1-mediated seed dormancy of Arabidopsis is regulated, at least in part, at the level of the AtDOG1 transcripts (Bentsink et al 2006).…”
Section: Discussionmentioning
confidence: 90%
“…AR7). Previous work has shown that: (1) AtDOG1 ‐mRNA remains present in AR dry seeds although its transcript levels quickly drop during imbibition (Bentsink et al , Nakawayashi et al ); (2) AtDOG1, with an estimated molecular mass of 40 kDa, is localized in the nuclei of the embryo, accumulates during seed maturation and remains stable during AR (Nakawayashi et al ); (3) AtDOG1 protein levels in freshly harvested seeds correlate with the AR time required to relieve dormancy (Nakawayashi et al , Graeber et al ); (4) BnaDOG1 ‐mRNA was also detected during seed maturation of B. napus despite its very low level of primary dormancy suggesting that the DOG1 expression is not sufficient for dormancy induction (Née et al ); (5) LesaDOG1 has functions beyond seed dormancy (i.e. sensu stricto germination; Graeber et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Murphey et al [19] proposed that DOG1 is a relevant gene in the induction of SD in response to temperatures. In some seeds, DOG1 induces SD because of the warm and prolonged cold stratification Plants 2020, 9, 480 5 of 20 in the course of seed imbibition [20,39]. Finch-Savage and Footitt indicated in their recent update on PD [34] that the thermo-inhibition of germination was DOG1 dependent and not reliant on an increased amount of ABA in lab conditions; while DOG1 is of decisive importance to dormancy cycling in field conditions in addition to its importance in determining the extent of PD.…”
Section: Dog1 In Seed Maturation and Dormancymentioning
confidence: 99%